The Authentic Athletic-Academic Model:: An Interdisciplinary Approach to Educate and Empower Alternative High School Students - Hall, LaTreese V. (Journal of Interdisciplinary Studies in Education, 2019)
Over the past 50 years, the number of alternative schools for at-risk students have increased exponentially. However, the research concerning the students that attend these institutions has been, at best, unhurried. Even more wanting is the research regarding the development and critical evaluation of educational interventions that can motivate and educate these students. The purpose of this paper is to propose an original, interdisciplinary framework aimed at increasing the positive student outcomes of alternative high school students. Drawing on the insights of sociology, psychology, and athletics, the “Athedemic” (Authentic Athletic-Academic) model integrates authentic teaching of academic subjects, athletics, social and emotional learning, and health for a more comprehensive educational approach to improve the student experience and empower youth in alternative educational settings. Future directions of alternative school research are considered.